1970
DOI: 10.1182/blood.v36.5.566.566
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Autophagic Vacuoles by Human Erythrocytes Physiological Role of the Spleen

Abstract: Using interference-contrast microscopy, erythrocyte vacuoles can be rapidly and easily distinguished. Because of the shadowing effect inherent in this optical system they appear as surface indentations. Twenty splenectomized patients with both normal and abnormal erythropoiesis had 54.3 per cent vacuolated cells as compared to 2.1 per cent in a control group of normal adults. A splenectomized patient with pure red cell aplasia, whose erythrocyte mass was maintained with fresh normal blood, had 44 per cent vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 14 publications
3
45
0
1
Order By: Relevance
“…However, membrane protusions (blebs) are observed in a proportion of cultured reticulocytes suggesting that membrane loss occurs by blebbing. Plasma membranecontaining cytosolic vesicles and plasma membrane blebs are also observed in reticulocytes circulating in the peripheral blood of splenectomized patients suggesting that final maturation of reticulocytes to erythrocytes in vivo involves passage through the spleen in normal individuals [9][10][11].These results provide evidence to support the view that production of cultured red cells for therapy is an achievable goal. The major challenge ahead is to develop a process capable of manufacturing cultured red cells in therapeutic quantities.…”
supporting
confidence: 53%
“…However, membrane protusions (blebs) are observed in a proportion of cultured reticulocytes suggesting that membrane loss occurs by blebbing. Plasma membranecontaining cytosolic vesicles and plasma membrane blebs are also observed in reticulocytes circulating in the peripheral blood of splenectomized patients suggesting that final maturation of reticulocytes to erythrocytes in vivo involves passage through the spleen in normal individuals [9][10][11].These results provide evidence to support the view that production of cultured red cells for therapy is an achievable goal. The major challenge ahead is to develop a process capable of manufacturing cultured red cells in therapeutic quantities.…”
supporting
confidence: 53%
“…A distinction between true vacuoles and surface invaginations cannot be made by LM, and this led to the initial description of pocked erythrocytes by Holroyde et al [6]. The same authors later used TEM and found that pocked erythrocytes were largely optical illusions that reflect the presence of intraerythrocytic vacuoles [30]. The term "pitted" or "pocked" RBC, however, is still in use [5,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Holroyde and Gardner [30] have shown that vacuoles large enough to be visible by LM are formed de novo in RBCs transfused to a splenectomized patient with pure red cell aplasia, i.e., with no production of his own RBCs. RBCs from a splenectomized patient were cleared of their LMvisible vacuoles within a few days when transfused to a recipient with an intact spleen [30]. These observations are in agreement with the above discussions on the mechanism of formation of large vacuoles and their clearance by the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Radioisotopic studies have shown that when the intraerythrocytic inclusions are siderotic granules, the spleen selectively removes the organelles while allowing the remainder of the cell to reseal and to circulate intact [19]. It has also been suggested [18], but prior to this report not conclusively proven, that the disappearance of pocked RBCs from the circulation involves removal only of the organelle and not the entire cell.…”
Section: Discussionmentioning
confidence: 83%